The Ash family : a novel - Dektar, Molly (Simon & Schuster, 2019)
At nineteen, Berie encounters a seductive and mysterious man at a bus station near her home in North Carolina. Shut off from the people around her, she finds herself compelled by his promise of a new life. He ferries her into a place of order and chaos: the Ash Family farm. There, she joins an intentional community living off the fertile land of the mountains, bound together by high ideals and through relationships she can<U+2019>t untangle. Berie<U+2014>now renamed Harmony<U+2014>renounces her old life and settles into her new one on the farm. She begins to make friends. And then they start to disappear.